HUBUNGAN MODAL SOSIAL PETANI TERHADAP KEBERLANJUTAN USAHATANI JAGUNG KUNING DI DESA WAKADIA KECAMATAN WATOPUTE KABUPATEN MUNA - Sari, Rati Dewisna; Taufik, Yani; Salahuddin, Salahuddin (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2024)
The objective of this study is to ascertain the correlation between farmers' social capital and the sustainability of yellow corn farming in Wakadia Village, Watopute Subdistrict, Muna Regency. The study population consisted of all yellow corn farmers in Wakadia Village, Watopute Subdistrict, Muna Regency, comprising a total of 103 households. The number of samples was determined using the Slovin formula with a 10% error margin, resulting in a sample size of 51 respondents. The sampling technique employed was simple random sampling. The data collection techniques employed included surveys, interviews, and document analysis, with data collected using questionnaires. This study employs two variables: social capital, comprising trust, participation, networks, and social norms, and farm sustainability, encompassing economic, social, and environmental sustainability. The data were subjected to descriptive analysis using a class interval formula and a Rank Spearman correlation formula. The findings indicate that the social capital of farmers engaged in yellow corn farming in Wakadia Village, Watopute Subdistrict, Muna Regency is in an optimal category, suggesting that their social capital is capable of sustaining yellow corn farming over the long term. The sustainability of yellow corn farming in Wakadia Village is sufficient, indicating that farmers have implemented business sustainability indicators but still require improvement. There is a significant and positive relationship between farmers' social capital and yellow maize business sustainability in Wakadia Village.